Degenerate photons from a cryogenic spontaneous parametric down-conversion source - Lange, Nina Amelie; Schapeler, Timon; Höpker, Jan Philipp; Protte, Maximilian; Bartley, Tim (Physical Review A)

Emission enhancement of erbium in a reverse nanofocusing waveguide - Güsken, Nicholas Alexander; Fu, Ming; Zapf, Maximilian; Nielsen, Michael P.; Dichtl, Paul; Röder, Robert; Clark, Alex S.; Maier, Stefan A.; Ronning, Carsten; Oulton, Rupert F. (Nature Communications)
Abstract Since Purcell’s seminal report 75 years ago, electromagnetic resonators have been used to control light-matter interactions to make brighter radiation sources and unleash unprecedented control over quantum states of light and matter. Indeed, optical resonators such as microcavities and plasmonic antennas offer excellent control but only over a limited spectral range. Strategies to mutually tune and match emission and resonator frequency are often required, which is intricate and precludes the possibility of enhancing multiple transitions simultaneously. In this letter, we report a strong radiative emission rate enhancement of Er 3+ -ions across the telecommunications C-band in a single plasmonic waveguide based on the Purcell effect. Our gap waveguide uses a reverse nanofocusing approach to efficiently enhance, extract and guide emission from the nanoscale to a photonic waveguide while keeping plasmonic losses at a minimum. Remarkably, the large and broadband Purcell enhancement allows us to resolve Stark-split electric dipole transitions, which are typically only observed under cryogenic conditions. Simultaneous radiative emission enhancement of multiple quantum states is of great interest for photonic quantum networks and on-chip data communications.

Nonlinear Dielectric Nanoresonators and Metasurfaces: Toward Efficient Generation of Entangled Photons - Sharapova, Polina R.; Kruk, Sergey S.; Solntsev, Alexander S. (Laser & Photonics Reviews)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Zwischen fortgesetzter Professionalisierung und bewusster Neuorientierung: Das außerschulische Berufsfeldpraktikum (BFP) aus Sicht von Lehramtsstudierenden - Truong, Ha My; Vogelsang, Christoph; Meier, Jana
Das obligatorische vierwöchige Berufsfeldpraktikum (BFP) für Lehramtsstudierende in Nordrhein-Westfalen verfolgt zwei Ziele. Zum einen sollen die Studierenden berufliche Perspektiven außerhalb des Schuldienstes kennenlernen (Bauer et al., 2011), zum anderen aber auch „Einblicke in die für den Lehrerberuf relevanten außerschulischen Tätigkeitsfelder“ (LABG, 2002, §12) erhalten. Diese Ziele sind zum Teil gegenläufig und können abhängig von der konkreten Ausgestaltung (z.B. in welchem Tätigkeitsfeld das BFP absolviert wird) nicht gleichzeitig voll erreicht werden. Es stellt sich daher die Frage, welcher Zielschwerpunkt von den Studierenden selbst angestrebt wird. Basierend auf kumulierten Daten von regelmäßigen Online-Evaluationsbefragungen zum BFP an der Universität Paderborn (N = 3.156) wird daher exploriert, wie Studierende das BFP ausgestalten und einschätzen. Es zeigt sich, dass das BFP generell als positiv beurteilt wird. In den gewählten Tätigkeitsfeldern und Rückmeldungen der Studierenden wird aber auch deutlich, dass das BFP eher als fortgesetzte Professionalisierung für den Lehrberuf und wenig zur Suche nach beruflichen Alternativen genutzt wird. Es wird also konsistent zur bekannt starken Motivation von LA-Studierenden für den Zielberuf ausgestaltet (Rothland, 2010). Dabei besteht allerdings die Gefahr, dass diese kaum bewusste Erfahrungen in einer Arbeitswelt machen, für die sie ihre Schüler*innen vorbereiten müssen (Dreer, 2013).

Level Up! Gamification in der Lehrkräfteausbildung (Poster) - Truong, Ha My
Mit Gamification wird der Einsatz von Spielemechanismen und -designs in nicht-spielerischen Situationen bezeichnet (Werbach, K.; Hunter, D., 2020). Die möglichen Ziele sind dabei, das Verhalten zu verändern und die Motivation zum Lernen sowie die Fähigkeit zur Problemlösung zu erhöhen. (Fischer, S.; Reichmuth, A., 2020) „Gamification kann als eine Bereicherung in Schule und Unterricht verstanden werden, insofern sie gutgestaltet sowie durchdacht und bedarfsgerecht eingesetzt wird“ (Sailer, M.; Tokls, D.; Mandl, H., 2019). Um angehende Lehrkräfte dabei zu unterstützen, das volle Potenzial von Gamification (GF) und Game-based Learning (GBL) in ihrem zukünftigen Unterricht auszuschöpfen, wird im Seminar "Spielend lernen? - Game-based Learning und Gamification im Schulkontext" eine umfassende Einführung in diese Konzepte geboten. Dabei werden nicht nur theoretische Grundlagen vermittelt, sondern den Studierenden die Möglichkeit gegeben, verschiedene Gamification-Methoden praktisch anzuwenden und zu erleben. Durch den Einsatz der moodle-basierten Plattform PANDA können verschiedene GF-Methoden und Beispiele für GBL nahtlos in das Seminar integriert werden. Dadurch haben die Teilnehmenden die Möglichkeit, die Konzepte von GF und GBL nicht nur theoretisch zu erlernen, sondern sie auch durch eigenes Erleben und praktisches Anwenden zu vertiefen.

Wie organisiert sind Lehramtsstudierende in ihrer Semester- und Prüfungsphasenplanung? – Entwicklung einer Evaluation zum Selbstorganisationsverhalten - Truong, Ha My

Brown representability for triangulated categories with a linear action by a graded ring - Letz, Janina Carmen (Arch. Math. (Basel))

The spectrum of a well-generated tensor-triangulated category - Krause, Henning; Letz, Janina Carmen (Bull. Lond. Math. Soc.)

Nachhaltigkeit in der Bildung fOERdern: Open Educational Resources in der Hochschullehre - Weber, Tassja (Inverted Classroom and beyond 2023: Agile Didaktik für nachhaltige Bildung)

Korpora für Deutsch als Fremdsprache – Potenziale und Perspektiven - Weber, Tassja; Flinz, Carolina; Mell, Ruth; Möhrs, Christine (Korpusgestützte Sprachanalyse. Grundlagen, Anwendungen und Analysen)

Real objects as a reason for mathematical reasoning - A comparison of different task settings - Jablonski, S

Is it all about the setting? — A comparison of mathematical modelling with real objects and their representation - Jablonski, Simone (Educational Studies in Mathematics)
Abstract Mathematical modelling emphasizes the connection between mathematics and reality — still, tasks are often exclusively introduced inside the classroom. The paper examines the potential of different task settings for mathematical modelling with real objects: outdoors at the real object itself, with photographs and with a 3D model representation. It is the aim of the study to analyze how far the mathematical modelling steps of students solving the tasks differ in comparison to the settings and representations. In a qualitative study, 19 lower secondary school students worked on tasks of all three settings in a Latin square design. Their working processes in the settings are compared with a special focus on the modelling steps Simplifying and Structuring, as well as Mathematizing. The analysis by means of activity diagrams and a qualitative content analysis shows that both steps are particularly relevant when students work with real objects — independent from the three settings. Still, differences in the actual activities could be observed in the students’ discussion on the appropriateness of a model and in dealing with inaccuracies at the real object. In addition, the process of data collection shows different procedures depending on the setting which presents each of them as an enrichment for the acquisition of modelling skills.

Komponierte Ambiguität. Ein anderer Blick auf polyphone Messen des 15. und 16. Jahrhunderts - Höink, Dominik (Kirchenmusikalisches Jahrbuch)

Teaching and Learning of Geometry-A Literature Review on Current Developments in Theory and Practice - Jablonski, S; Ludwig, M

How digital tools support the validation of outdoor modelling results - Jablonski, S; Barlovits, S; Ludwig, M

Gendersensible Bildung als ein Thema von vielen im Lehramtsstudium: Das Profil Umgang mit Heterogenität als freiwillige Zusatzqualifikation - Decker, Claudia; Westphal, Petra

Realization of a Multi-Output Quantum Pulse Gate for Decoding High-Dimensional Temporal Modes of Single-Photon States - Serino, Laura; Gil López, Jano; Stefszky, Michael; Ricken, Raimund; Eigner, Christof; Brecht, Benjamin; Silberhorn, Christine (PRX Quantum)
Keywords: General Physics and Astronomy; Mathematical Physics; Applied Mathematics; Electronic; Optical and Magnetic Materials; Electrical and Electronic Engineering; General Computer Science

Protein–protein interactions in solutions of monoclonal antibodies probed by the dependence of the high-frequency viscosity on temperature and concentration - Rott, Emily; Leppin, Christian; Diederichs, Tim; Garidel, Patrick; Johannsmann, Diethelm (The Analyst)
 A QCM-D probes the temperature- and concentration-dependent complex high-frequency viscosity and provides information on protein-protein interactions in solutions of monoclonal antibodies.

Stiffness of Contacts between Adsorbed Particles and the Surface of a QCM‐D Inferred from the Adsorption Kinetics and a Frequency‐Domain Lattice Boltzmann Simulation - Johannsmann, Diethelm; Leppin, Christian; Langhoff, Arne (Advanced Theory and Simulations)
Abstract A simulation based on the frequency‐domain lattice Boltzmann method (FreqD‐LBM) is employed to predict the shifts of resonance frequency, Δ f , and half bandwidth, ΔΓ, of a quartz crystal microbalance with dissipation monitoring (QCM‐D) induced by the adsorption of rigid spheres to the resonator surface. The comparison with the experimental values of Δ f and ΔΓ allows to estimate the stiffness of the contacts between the spheres and the resonator surface. The contact stiffness is of interest in contact mechanics, but also in sensing because it depends on the properties of thin films situated between the resonator surface and the sphere. The simulation differs from previous implementations of FreqD‐LBM insofar, as the material inside the particles is not included in the FreqD‐LBM algorithm. Rather, the particle surface is configured to be an oscillating boundary. The amplitude of the particles' motions (displacement and rotation) is governed by the force balance at the surface of the particle. Because the contact stiffness enters this balance, it can be derived from experimental values of Δ f and ΔΓ. The simulation reproduces experiments by the Krakow group. For sufficiently small spheres, a contact stiffness can be derived from the comparison of the simulation with the experiment.

Effect of Noise on Determining Ultrathin-Film Parameters from QCM-D Data with the Viscoelastic Model - Johannsmann, Diethelm; Langhoff, Arne; Leppin, Christian; Reviakine, Ilya; Maan, Anna M. C. (Sensors)
Quartz crystal microbalance with dissipation monitoring (QCM-D) is a well-established technique for studying soft films. It can provide gravimetric as well as nongravimetric information about a film, such as its thickness and mechanical properties. The interpretation of sets of overtone-normalized frequency shifts, ∆f/n, and overtone-normalized shifts in half-bandwidth, ΔΓ/n, provided by QCM-D relies on a model that, in general, contains five independent parameters that are needed to describe film thickness and frequency-dependent viscoelastic properties. Here, we examine how noise inherent in experimental data affects the determination of these parameters. There are certain conditions where noise prevents the reliable determination of film thickness and the loss tangent. On the other hand, we show that there are conditions where it is possible to determine all five parameters. We relate these conditions to the mathematical properties of the model in terms of simple conceptual diagrams that can help users understand the model’s behavior. Finally, we present new open source software for QCM-D data analysis written in Python, PyQTM.